SAAT REVIEW ONLINE MENENTUKAN: Citra Merek Dan Kualitas Produk Menggiring Konsumen Memutuskan Pembelian Skincare - Hafizni, Rihan; Natoil, Natoil; Pekerti, Vinko Satria (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
The increasing interest of society in skincare products encourages companies to pay attention to factors that influence consumer purchasing decisions. Digital information, brand image, and product quality become important considerations in determining consumer preferences. This study aims to determine the influence of electronic word of mouth, brand image, and product quality on purchasing decisions of Skintific skincare products in Semarang City. The population in this study consists of users of Skintific skincare products residing in Semarang City, with the total number of population unknown. The sample in this research amounted to 78 respondents, determined using purposive sampling based on 13 research indicators. Data were collected through questionnaires using a Likert scale, and the data were analyzed using multiple linear regression with SPSS. The results show that the electronic word of mouth variable does not have a significant effect on purchasing decisions, with a significance value of 0.673 (>0.05), a regression coefficient of 0.064, and a t-value of 0.424. The brand image variable has a significant effect on purchasing decisions, with a significance value of 0.001 (<0.05), a regression coefficient of 0.545, and a t-value of 3.408. The product quality variable also has a significant effect on purchasing decisions, with a significance value of 0.000 (<0.05), a regression coefficient of 0.733, and a t-value of 5.749. The coefficient of determination (Adjusted R Square) of 0.697 indicates that brand image and product quality explain 69.7% of the variation in purchasing decisions, while the remaining percentage is influenced by variables outside this study. Suggestions for future research include considering other variables that may influence purchasing decisions, increasing the number of samples, and expanding the scope of respondents to obtain more comprehensive results.